The ability of teleost fishes to recognize individual faces suggests an early evolutionary origin in vertebrates - Masanori Kohda; Shumpei Sogawa; Will Sowersby (Frontiers in Psychology, 2024)
The face is the most important area on the human body for visually differentiating between individuals. When encountering another person, humans initially gaze at and perceive the face holistically, utilizing first-order relational information and specific neural systems. Information such as identity and emotional state are then obtained from the face by distinguishing between small inter-individual differences, i.e., second-order relational information. Similar patterns and mechanisms underlying individual face recognition have been documented in primates, other social mammals, birds, and more recently in some fishes. Like humans, fish are capable of rapidly (<0.5 s) and accurately recognizing multiple familiar conspecifics by individual-specific variation in the face. Fish can also recognize faces from various distances and angles, providing evidence for mental representation of faces in this large and diverse vertebrate group. One species, the cleaner fish, has even demonstrated mirror self-recognition (MSR) via self-face recognition, strengthening the claim that non-human animals are capable of having mental images and concepts of faces. Here, we review the evidence for individual face recognition in fishes and speculate that face identification neural networks are both similar and widespread across vertebrates. Furthermore, we hypothesize that first-and second-order face recognition in vertebrates originated in bony fishes in the Paleozoic era ~450 Mya, when social systems first evolved, increasing the importance of individual recognition.